Soaring Fuel Prices: Sentiments of Filipinos on Excise Tax - Caballo, John Harry; G. Baradillo, PhD, Danilo (International Journal on Orange Technologies, 2025)
This study analyzed the sentiments of 100 Facebook comments on excise tax using Orange Software. Using the word cloud feature, the top 10 are chosen from the list of frequently used words with at least fifteen instances in the hundred Facebook comments. In the sentiment analysis, the Facebook comments were analyzed as positive, negative, or neutral. Based on the results, 52% of the comments showed positive sentiment, 41% displayed negative sentiment, and 7% expressed neutrality on the issue. In the qualitative analysis of the sentiments, two positive sentiments were extracted, which are: excise tax aids the operations of the government and excise tax subsidizes the transport and business sector. For the negative sentiments, three themes were extracted: excise tax suspension addresses inflation, the government has no concern for its citizens, and leaders are ineffective and corrupt. Positive sentiments demonstrate public support for the excise tax. It is considered essential for government revenues, and suspending it could have significant economic consequences. However, negative sentiments stem from concerns about inflation, distrust in leadership, and perceptions of corruption within the government.